From Paracetamol to Rolipram and Derivatives: Application of Deacetylation–Diazotation Sequences and Palladium-Catalyzed Matsuda–Heck Reaction - Schmidt, Bernd; Elizarov, Nelli; Berger, René; Petersen, Monib H. (Synthesis, 2013)
A six-step synthesis of the antidepressant rolipram from the popular analgetic 4-acetamidophenol (paracetamol) is described. The steps include oxidative functionalization of the aromatic core, diazonium salt formation via deacetylation-diazotation, Matsuda–Heck reaction, conjugate addition of nitromethane, and hydrogenative cyclization.
Keywords: acetanilides; deacetylation; diazonium salts; palladium; Matsuda–Heck reaction